Uncertainties on the combined use of ICESat and ICESat-2 observations to monitor lake levels - Luo, Shuangxiao; Song, Chunqiao (Frontiers in Water, 2023)
Lake water level is an important variable to indicate the lake hydrological balances and climate change impacts. Benefiting from the launch of the laser altimeters ICESat and ICESat-2, the higher spatial-resolution elevation measurements open new possibilities for monitoring lake levels globally over the past two decades. However, uncertainties on the combined use of two-generation satellite laser measurements have not yet been investigated specifically. This study aims to summarize the important technique notes on the water level data processing by integrating the ICESat and ICESat-2 altimetry measurements. We mainly focus on the effect of geoid height, water mask for extracting altimetry footprints, and the nine-year data gap between the two generations of satellites on water-level change estimates. We compared the influences of the above three factors in different situations by selecting typical lakes worldwide as study cases. The results show that: 1) In the combination of ICESat and ICESat-2 products, geoid heights need to be recalculated for each footprint based on its longitude and latitude in order to replace the geoid values of the original products when calculating orthometric heights. It is necessary because the default geoids in both generations of products (ICESat and ICESat-2) exhibit a systematic deviation; 2) To balance the accuracy and efficiency, the small water mask in the low-level year is recommended to extract the potential footprints, in comparison with the laborious processing of time-varying water masks; 3) The nine-year data gap between ICESat and ICESat-2 observations may cause inevitable overestimations or underestimations of long-term change rate of lake levels with nonlinear trajectory, yet has few effects on lakes with (near) linear trending or fluctuating changes.